Effect of Dilution and Electrolysis Time on Recovery of Mg2+ As Mg(OH)2 from Bittern by Electrochemical Method - Hanif Amrulloh; Wasinton Simanjutak; Rudy Tahan Mangapul Situmeang; Sophia Lasma Sagala; Rikha Bramawanto; Ridho Nahrowi (The Journal of Pure and Applied Chemistry Research, 2019)
This research was conducted to study the effect of dilution and electrolysis time on therecovery of Mg2+as Mg(OH)2from bittern by electrochemical method. The electrochemical process was carried out using 2-compartment electrochemical cell, connected by salt bridge prepared from NaCl suspended in gelatin. The experiment was carried out using nickel as cathode and carbon as an anode. The electrolysis process was carried out at a potential of 18 volts with dilution factors of 0, 2, 4, 6, and 8 times, and electrolysis time of 1, 2, 4, 6, 8, 10, and 12 hours. The results show that percent of conversion increased with dilution with the best result was obtained at 4x dilution factor and 4 hours electrolysis time with percent conversion of 85 % and purity of Mg(OH)291%